A CLINICAL CASE OF ESOPHAGEAL PERFORATION IN A PATIENT WITH PHARYNGEAL-ESOPHAGEAL DIVERTICULUM (CENKER) - Павленко, Владимир Вячеславович; Фролов, Павел Александрович; Каменева, Евгения Александровна; Лупивок, Арина Игоревна; Кокоулина, Юлия Андреевна (Medicine in Kuzbass, 2025)
The article presents a clinical case of esophageal perforation in a patient with pharyngeal-esophageal diverticulum (Cenker), which is a rare and potentially life-threatening condition. The mortality rate for non-surgical treatment of esophageal perforations is 20-38%.
Keywords: pharyngeal-esophageal diverticulum; Cenker's diverticulum; esophageal perforation; EGDS